(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
Thanks to the latest developments in digital dentistry, research into methods and materials for three-dimensional (3D) printing is actively underway. We report on the clinical application and results of 3D printing temporary crowns made of polylactic acid (PLA) using a fused deposition (FDM) printer. Five participants were recruited from among patients who were scheduled to undergo treatment using a single full-coverage crown at the University Medical Center’s dental clinic from June to August 2022. As temporary crowns, we used 3D printed crowns made of PLA using an FDM printer. were evaluated for discomfort, fractures, and displacements. Temporary 3D printed crowns were preserved without fractures, displacement, or discomfort until the permanent prosthesis was ready. The average time it took to print temporary crowns was about 7 minutes. 3D printing temporary PLA crowns on an FDM printer is a convenient process for dentists. However, these crowns have some limitations, such as rough surface texture and transparency; therefore, the 3D printing process needs to be improved to produce better prosthetics.